DIVERSI DALAM PENYELESAIAN PERKARA PIDANA ANAK MELALUI PENDEKATAN RESTORATIVE JUSTICE - Sofhan, Dedi; Widjajanti, Ermania (Ensiklopedia of Journal, 2024)
Abstract: The implementation of diversion in criminal cases involving children is an essential effort to prevent children from experiencing the negative effects of resolving criminal cases through the criminal justice system. This study aims to analyze and understand the application of diversion in resolving juvenile criminal cases through a restorative justice approach. It seeks to identify various forms of diversion that can be applied in juvenile legal processes and how restorative justice can contribute to restoring relationships among offenders, victims, and the community. This research employs a normative legal research method, focusing on positive legal norms, particularly those contained in applicable legislation. The findings reveal that diversion in resolving juvenile criminal cases through a restorative justice approach offers a better solution. Diversion is conducted with the aim of achieving reconciliation between the victim and the juvenile offender. This process seeks to resolve juvenile cases outside the formal judicial system to prevent negative impacts on the child’s development. The implementation of diversion is expected to safeguard the future of children involved in legal processes. The goal of diversion through a restorative justice approach is not merely to impose punishment but to create deeper balance and justice while repairing the relationship between the victim and the offender. This can be achieved through mutual agreements. In this process, victims are given the opportunity to express their losses, while offenders are provided a chance to make amends through compensation, reconciliation, or other mutually agreed-upon solutions.Keywords: Diversion, Juvenile Justice, Restorative Justice.